Synthesis and IR spectra of O-ethyl/O,O-diethyl O/S Alkyl Benzimidazolyl-2 Phosphorothioates - Vyas, P.C.; Vyas, Sushma; Vyas, P. (Asian Journal of Chemistry, 2010)
O-ethyl O/S alkyl benzimidazolyl-2-phosphorothioates and O,O-diethyl O/S alkyl benzimidazolyl-2 phosphorothioates derivatives have been synthesized by reacting O-ethylthiophosphorylchloride or O,O-ethylthiophosphorylchloride respectively with 2-hydroxy/mercapto alkyl benzimidazoles in various molar ratios. The potassium hydrogen carbonate/potassium carbonate was added as an acid scavenger in the above reactions. These O-ethyl/O,O-diethyl, O/S alkyl-benzimidazolyl-2 substituted phosphorothioate derivatives were characterized by elemental analysis, thin layer chromatographic and infrared spectral studies.